Islamic Legal Perspectives on Climate Change and Global Policy Frameworks - Jasim Mohammed Hussein; Sawsan Khairy Abdullah; Zahraa Mahdi Dahash; Mohammed Zuhair; Asanalieva Meergul Maksutalievna (Al-Istinbath: Jurnal Hukum Islam)
This article explores the intersection of climate change and Islamic law, analyzing how Sharia principles may enhance and support global environmental policies. The study aims to address the urgent need for ethical frameworks in environmental action by examining Islamic jurisprudence’s approach to stewardship (Khilafah), justice (Adl), and protection for vulnerable populations. Using a comprehensive literature review and case studies, this research investigates the relevance of Islamic law and international legislation on climate change. Islamic principles offer unique perspectives on environmental governance that prioritize equity and communal responsibility, bridging gaps in existing global policy frameworks. Findings reveal that integrating Sharia-based ethics can promote more inclusive and justice-oriented climate policies. This integrative approach underscores the potential of Islamic legal principles to strengthen and diversify international climate action, contributing to more equitable and effective solutions. By incorporating Islamic legal concepts, this study provides insights into developing a robust, ethical foundation for global climate governance.